Marketing Mix Terhadap Kepuasan Konsumen pada Mama-Mama Penjual Noken di Oyehe Kabupaten Nabire - Camelia Praestuti (Universitas Sam Ratulangi, 2020)
Marketing Mix is a number of marketing tools used by business people to convince the object of marketing or target market. Noken Papua is a distinctive attribute of Papua origin with various forms ranging from headdresses, clothes, skirts, accessories, shoes, and bags of Noken which are very popular widely in every corner of the village to the city in the land of Papua. Each Noken product produced can be seen as the result of the level of consumer satisfaction that consumes it where every consumer consumes, look at the shape and model, price, and quality of these Noken products.